2004
DOI: 10.1007/s00425-004-1353-z
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of inner cell wall layers after manipulations to reduce tensile stress: observations and interpretations for stress transmission

Abstract: The inner layer of the cell wall in tissues that are under tensile stress in situ, e.g. epidermis and collenchyma of etiolated sunflower hypocotyls, shows a pattern of transverse folds when the tissues are detached and plasmolysed. This can be observed by Nomarski imaging of inner surfaces of the outer cell walls and electron microscopy of longitudinal sections after peeling the epidermis and bathing it in plasmolysing solutions. The folds are apparently caused by buckling of the inner layer due to the longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…As a consequence, when the wall is elongating rapidly the extensional stress is distributed nonuniformly through the wall, with a maximum close to the outer wall (Figure 5). This is consistent with observations (Hejnowicz and Borowska-Wykret, 2005) showing how relaxation of tensile stress (via detachment) induces buckling of the inner wall of sunflower hypocotyl, indicating that the outer wall transmits the majority of the tensile stress in the wall.…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence, when the wall is elongating rapidly the extensional stress is distributed nonuniformly through the wall, with a maximum close to the outer wall (Figure 5). This is consistent with observations (Hejnowicz and Borowska-Wykret, 2005) showing how relaxation of tensile stress (via detachment) induces buckling of the inner wall of sunflower hypocotyl, indicating that the outer wall transmits the majority of the tensile stress in the wall.…”
Section: Discussionsupporting
confidence: 92%
“…Whether these conclusions about xyloglucan–cellulose interactions are unique to the onion epidermis or are generally applicable to other primary cell walls remains to be established by further work. The cross‐lamellate structure of these onion walls (Zhang et al ., ) resembles the outer (periclinal) epidermal walls of other organs (Hejnowicz and Borowska‐Wykret, ; Kutschera, ). In contrast, for the inner walls of the epidermis of Arabidopsis hypocotyls (Crowell et al ., ) and for internal cells of other stems (Baskin, ; Marga et al ., ) microfibril orientation is largely transverse.…”
Section: Discussionmentioning
confidence: 94%
“…S5 2 ). Previous investigations showed that such wrinkling is a manifestation of the wall layer buckling after the removal of tensile in-plane stress from the wall (Hejnowicz and Borowska-Wykrę t 2005;Lipowczan et al 2018). Because the orientation of wrinkles is related to the anisotropy of the wall strain, the wrinkling pattern may be used to assess the anisotropy of osmotically induced strain at the subcellular scale.…”
Section: Stress Removal Leads To Wrinkling Of Protoplast-facing Layermentioning
confidence: 99%
“…Moreover, in cells with rather thick walls, the removal of tensile stress leads to wrinkling of the wall surface that faces the protoplast. This is a manifestation of buckling of the youngest layers of the wall that results from a gradient in the elastic strain of wall layers, the values of which decreases in the direction toward the protoplast (Hejnowicz and Borowska-Wykrę t 2005;Lipowczan et al 2018).…”
Section: Introductionmentioning
confidence: 99%